2003
DOI: 10.5194/angeo-21-1467-2003
|View full text |Cite
|
Sign up to set email alerts
|

The location and rate of dayside reconnection during an interval of southward interplanetary magnetic field

Abstract: Abstract. Using ionospheric data from the SuperDARN radar network and a DMSP satellite we obtain a comprehensive description of the spatial and temporal pattern of dayside reconnection. During a period of southward interplanetary magnetic field (IMF), the data are used to determine the location of the ionospheric projection of the dayside magnetopause reconnection X-line. From the flow of plasma across the projected X-line, we derive the reconnection rate across 7 h of longitude and estimate it for the total l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 66 publications
4
63
0
1
Order By: Relevance
“…In a previous study, under purely southward IMF conditions, Phan et al [2000] had interpreted the repeated detection of reconnection jets emanating from an equatorial X-line by Equator-S and Geotail at the dawn flank magnetopause to signify the presence of a 40 Re X-line spanning the entire dayside equator. Although no in-situ measurements were made at other magnetopause locations (including the subsolar region), radar observations for the same event suggested the presence of such an extended Xline [Pinnock et al, 2003].…”
Section: Component Merging and The Extent Of The X-linementioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, under purely southward IMF conditions, Phan et al [2000] had interpreted the repeated detection of reconnection jets emanating from an equatorial X-line by Equator-S and Geotail at the dawn flank magnetopause to signify the presence of a 40 Re X-line spanning the entire dayside equator. Although no in-situ measurements were made at other magnetopause locations (including the subsolar region), radar observations for the same event suggested the presence of such an extended Xline [Pinnock et al, 2003].…”
Section: Component Merging and The Extent Of The X-linementioning
confidence: 99%
“…Remote sensing methods have indicated the presence of an X-line spanning a large portion of the dayside magnetopause during southward IMF [Fuselier et al, 2002;Pinnock et al, 2003], but this has not been confirmed by in-situ measurements. Establishing the presence of extended X-lines in the magnetosphere by in-situ measurements requires the presence of widely separated multi-spacecraft detecting the same reconnection events.…”
Section: Introductionmentioning
confidence: 99%
“…13 The spatial variation (with MLT) of remote measurements of the magnetopause reconnection rate made from the ionosphere using SuperDARN observations. (a) The reconnection rate variation during an interval of due southward IMF from 1330 to 1400 UT on February 11, 1998 (from Pinnock et al 2003). (b) The reconnection rate variation during an interval of due northward IMF from 1440 to 1520 UT on November 11, 1998 (from Chisham et al 2004b).…”
Section: Reconnection Rate Measurementsmentioning
confidence: 99%
“…Separating the contributions from magnetopause and magnetotail reconnection using SuperDARN measurements of the reconnection rate in the dayside ionosphere, Milan et al (2003b) showed that nightside reconnection following the first substorm lasted less than 200 min, and likely only 100 min-the duration of the recovery phase of the first substorm. Pinnock et al (2003) studied the extent, and spatial and temporal variation of magnetopause reconnection during steady due southward IMF. They derived the ionospheric projection of the magnetopause reconnection rate across the dayside ionosphere, as summarized in Fig.…”
Section: Reconnection Rate Measurementsmentioning
confidence: 99%
“…Pinnock et al, 2003) and proton aurora images (e.g. have provided indirect evidence for continuous reconnection lasting many hours.…”
Section: Introductionmentioning
confidence: 99%